Study of the Use of Yeast Types and Soaking Time on the Quality of Cocoa Beans (Theobroma cacao L.) - Paramuji, Muji; Wanbahroni Jiwar Baru; Wahyu Syahputra (Talenta Publisher, 2022)
The quality of cocoa beans at the farmer level is very low. The main factor that makes the quality of cocoa is low, it of which is fermentation. Improved fermentation will improve the quality of the cocoa beans produced. This study aims to examine the effect of the use of yeast types and soaking time on the quality of cocoa beans. This research has been carried out in the laboratory of the Faculty of Agriculture UISU Medan using a factorial Completely Randomized Design (CRD), which consists of two factors, namely: Factor I type of yeast (R) consisting of 4 levels: R0 = Control; R1 = Bread Yeast; R2 = Tempeh Yeast and R3 = Tape Yeast. Factor II The immersion time (P) consists of 4 levels: P1 = 1 hour; P2 = 2 hours; P3 = 3 hours and P4 = 4 hours with 2 repetitions. Parameters observed were yield, pH, water content, fat content, and organoleptic test of taste and aroma. The data is analyzed using means of variance and if it had a significant effect, then continued with Duncan's Multiple Range Test (DMRT). The results of the study showed that the type of yeast had a significant effect on pH, water content, fat content, and organoleptic test values ​​for taste and aroma. Soaking time has significantly different effects on pH, fat content, and organoleptic test values ​​for taste and aroma. The interaction of the treatment the effect of yeast type and soaking time had no significant effect on all observed parameters. Fermentation of cocoa beans with the addition of yeast can improve the quality of cocoa beans, especially with the addition of baker's yeast and soaking time of 4 hours to produce the highest taste and aroma.